Bird-window collisions: different fall and winter risk and protective factors - Barbara B. Brown; Lia Hunter; Sabrina Santos (PeerJ, 2020)
Background To reduce bird fatalities from millions of window collisions each year in North America, it is important to understand how design and landscape elements relate to collision risk. The current study extends prior research that found that buildings near ornamental pear trees (Prunus calleryana) and buildings with mirrored windows significantly increased odds of collisions among eight buildings on the University of Utah campus in winter. The previous study found bird-friendly glass was not related to collision risk, although only one fatality occurred at two buildings with ORNILUX® ultraviolet (UV) or fritted windows. We reasoned that extending data collection to include fall might provide a better test of efficacy. We tested the following three hypotheses: (1) Buildings with mirrored windows would experience more collisions, replicating the original study; (2) the addition of fall migration data would reveal fewer collisions at the buildings with bird-friendly windows; (3) the danger of pear tree proximity would be heightened in winter, when fruit is ripe enough to appeal to frugivores, especially the Cedar Waxwings (Bombycilla cedrorum) that frequent these trees. Methods Trained observers monitored buildings three times per week in Fall (September 12 to October 27, 2019) and Winter (October 29, 2019 to January 24, 2020). Collisions were photographed and documented in the iNaturalist University of Utah Bird Window Collision Project. Results There were 39 total collisions, from 0 to 14 per building.Using generalized estimating equations, buildings near pear trees had 3.33-fold increased odds, mirrored windows had 5.92-fold increased odds, and bird-friendly windows had an 84% lower odds (Odds ratio = 0.16) of bird window collisions when analyzed separately; all were statistically significant (p < 0.01). A test of all possible combinations of risk and protective factors revealed that the best fit model included pear trees (odds = 2.31) and mirrored windows (odds = 2.33). A separate analysis tested the pear tree by season interaction model; it yielded the deadliest combination, with 40-fold increased odds for buildings near pear trees in winter season. Discussion This research provides the first peer-reviewed evidence found for the efficacy of bird-friendly fritted windows and ORNILUX ® UV windows in buildings. In addition, it replicated a study that established the dangers of mirrored windows and fruiting pear trees near buildings. These risks were especially dangerous to Cedar Waxwings, who constituted 62.2% of the identifiable window collision victims. This research highlights how building risks depend on window design, landscape choices, species, and season. If replicated, analyses of risk factors can help identify buildings that require mitigation to make existing windows less deadly. Results also support the installation of bird-friendly glass in new or renovated buildings to reduce fatalities.